Hydrogen evolution reaction catalyst
By dispersing catalytic metal materials such as nickel or cobalt and vanadium materials in the catalyst, the existing water decomposition catalysts have been solved, and efficient and low-cost hydrogen generation has been achieved.
Patent Information
- Application Number
- CN201980072014.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2018-10-29
- Filing Date
- 2019-10-29
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2039-10-29
AI Technical Summary
Among the existing water decomposition catalysts, Pt-based catalysts are expensive and unsustainable, making them difficult to meet the needs of large-scale applications, and there is instability in the nickel cathode due to passivation problems.
A hydrogen evolution reaction (HER) catalyst containing catalytic metal species such as nickel or cobalt and vanadium species has been developed to increase catalytic activity and prevent passivation by dispersing these substances in the catalyst.
It realizes efficient catalytic hydrogen generation in alkaline and neutral solutions, reduces the demand for overpotentials, improves the stability and activity of the catalyst, and provides low-cost and efficient cathode materials.
Smart Images

Figure BDA0003046471140000171 
Figure HDA0003046471150000011 
Figure HDA0003046471150000012
Abstract
Description
Technical Field
[0001] The present invention relates to a catalyst for hydrogen evolution reaction (HER) and a method of using the catalyst in a water splitting process. The present invention also provides a composition, a material and an electrode comprising the catalyst. Background Art
[0002] Water splitting processes are considered a sustainable method for hydrogen production and storage because they can utilize abundant available water and less carbon-intensive energy sources such as renewable energy (e.g., solar energy) as input. Water splitting can be performed in an electrolyzer to produce hydrogen at the cathode via the hydrogen evolution reaction (HER). Oxygen can be produced at the anode via the oxygen evolution reaction (OER). Current focus is on preparing catalysts for hydrogen evolution because hydrogen is more readily used as a fuel for a variety of applications, such as fuel cells.
[0003] Pt-based catalysts (e.g., Pt / C) are currently the main choice of cathode materials in water electrolyzers due to their extremely low overpotential (η) and large current density (j) at the onset of hydrogen evolution. However, Pt-based HER catalysts are expensive and have an unsustainable supply, making them unsuitable for large-scale applications.
[0004] Current work is focused on developing water splitting catalysts based on earth-abundant metals. Earth-abundant metals do not include Re, Ru, Os, Rh, Ir, Pd, Pt, Ag, and Au.
[0005] It has been shown that nickel cathodes can effectively catalyze HER. However, nickel cathodes are unstable due to the formation of a passivating cathode layer. Some reports have shown that the inclusion of vanadium oxide (V 2 O 5 ) can prevent the passivation of the nickel cathode. Over time, vanadium oxide deposits will form on the surface of the nickel cathode.
[0006] There is a continuing need to provide alternative HER catalysts. In particular, there is a need to develop catalysts based on earth-abundant transition metals. Summary of the invention
[0007] The present invention is based at least in part on the discovery that a catalyst of a metal catalyst material (e.g., Ni or Co) interspersed with a vanadium material increases the HER catalytic activity of the metal catalyst material. In addition, passivation of the metal catalyst material is prevented. Surprisingly, the vanadium-doped catalyst of the present invention also exhibits strong HER catalytic activity in alkaline and neutral solutions.
[0008] In one aspect, the present invention provides a hydrogen evolution reaction (HER) catalyst comprising:
[0009] catalytic metal material comprising an active catalyst material, and
[0010] Vanadium substances,
[0011] Among them, catalytic metal substances and vanadium substances are dispersed in the HER catalyst.
[0012] In another aspect, the present invention provides a catalytic material comprising the HER catalyst described herein and a substrate.
[0013] In another aspect, the present invention provides an electrode comprising a conductive substrate as described herein and a HER catalyst. The HER catalyst is typically coated (eg, by electrodeposition) onto the surface of the conductive substrate.
[0014] In another aspect, the present invention provides a method for preparing the HER catalyst described herein, the catalytic material described herein and / or the electrode described herein, the method comprising contacting a conductive substrate with a solution comprising a metal catalyst source and a vanadium source, and applying a voltage between the substrate and a counter electrode through the solution to electrodeposit the metal catalyst and the vanadium onto the surface of the conductive substrate.
[0015] In another aspect, the present invention provides a method for hydrogen evolution from water, the method comprising: providing an electrochemical cell comprising at least two electrodes and an electrolyte solution, contacting water with the at least two electrodes, and applying a voltage between the at least two electrodes, wherein at least one of the at least two electrodes comprises the HER catalyst described herein, the catalytic material described herein, or the electrode described herein.
[0016] In another aspect, the present invention provides an electrolyzer comprising at least two electrodes and a power supply, wherein at least one of the at least two electrodes comprises the HER catalyst of the present invention.
[0017] Before describing the present invention in detail, it is to be understood that this invention is not limited to the particular exemplary embodiments, methods of manufacture or use, which may, of course, vary.
[0018] The invention described and claimed herein has many attributes and embodiments, including but not limited to those set forth, described or referenced in the Summary of the Invention, which is not intended to be all-inclusive. The invention described and claimed herein is not limited to or by the features or embodiments identified in the Summary of the Invention, which are included only for purposes of illustration and not limitation in the Summary of the Invention.
[0019] All publications, patents and patent applications cited herein, whether supra or infra, are hereby incorporated by reference in their entirety.
[0020] It will be appreciated that if any prior art publication is referred to herein, this citation does not constitute an admission that the publication forms part of the common general knowledge in the art. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] The present application will be further described, by way of example only, with reference to the accompanying drawings, in which:
[0022] Figure 1 Shown are cyclic voltammetry curves on a fluorine-doped tin oxide (FTO) substrate immersed in a solution containing or not containing ammonium metavanadate.
[0023] Figure 2 Shown are a series of X-ray diffraction (XRD) patterns of various HER catalysts prepared according to Example 1 on fluorine-doped tin oxide (FTO) as a substrate.
[0024] Figure 3 Meaning: According to the general method of Example 1, different concentrations of NH 4 VO 3 A series of XRD diffraction patterns of NiCuVOx prepared from precursors.
[0025] Figure 4 ah represents: (a) a scanning electron microscope (SEM) image of the HER catalyst of the present invention; (b) a transmission electron microscope (TEM) image of the HER catalyst; (c) a high-resolution transmission electron microscope (HRTEM) image of the HER catalyst; (d) a high-angle annular dark field scanning transmission electron microscope (HAADF-STEM) image of the HER catalyst; (e)-(h) energy dispersive X-ray spectroscopy (TEM-EDS) mapping images of each HER catalyst of Ni, Cu, V and O atoms present in the HER catalyst.
[0026] Figure 5 ac represent: SEM images of (a) Ni, (b) NiCu, and (c) NiVOx electrodes prepared according to Example 1.
[0027] Figure 6 Shown are: X-ray photoelectron spectroscopy (XPS) spectra of (a) Ni2p, (b) Cu2p, (c) V2p and (d) O1s of the HER catalyst of the present invention.
[0028] Figure 7ad represent: (a) linear sweep voltammetry (LSV) curves of the HER catalysts of the present invention (NiCuVOx-measured values and internal resistance (iR) corrected values-and NiVOx) compared with their non-vanadium equivalents (NiCu and Ni) and Pt / C catalysts under alkaline conditions (1 M KOH, pH = 14); (b) Tafel plots of the HER catalysts of the present invention (NiCuVOx-measured values and internal resistance (iR) corrected values-and NiVOx) compared with their non-vanadium equivalents (NiCu and Ni) and Pt / C catalysts under alkaline conditions (1 M KOH, pH = 14); (c) multiple current curves of NiCuVOx; (d) chronopotentiometry curves of NiCuVOx and Ni electrodes.
[0029] Figure 8 a and b show the LSV curves of NiCuVOx obtained under different electrodeposition conditions in 1 M KOH: (a) different amounts of Cu precursor; and (b) different anodization times.
[0030] Fig. 9 Indicates: In 1M KOH, the electrolyte contains or does not contain NH 4 VO 3 LSV curve of NiCuVOx (Example 1) under the condition of .
[0031] Fig.10 ad represent: (a) LSV curves of NiCuVOx without iR compensation and control sample in 1.0M pH=7 phosphate buffer solution, the black dashed line is NiCuVOx after iR correction. (b) In 1.0M pH=7 phosphate buffer solution, the current density is 50mA cm -2 (c) Chronopotentiometry curve of NiCuVOx in seawater; (d) Chronopotentiometry curve of NiCuVOx in seawater.
[0032] Fig.11 Figure 3: Overpotential versus time for a NiCuVOx electrode coated with chromium oxide, showing stability and durability.
[0033] Fig.12 a and b show: (a) multiple current curves of NiCuVOx in 30 wt % KOH electrolyte at 80 °C compared with a nickel cathode (two-electrode electrolysis); (b) NiCuVOx at a current density of 300 mA cm -2 Chronopotentiometry curves of 10 cycles of power supply interruption (continuous electrolysis for 1 hour, then power off for 0.5 hour).
[0034] Fig.13ae represents: (a) TEM image of NiCuVOx (Example 1) after being used as a catalyst in a chronopotentiometry experiment (results are shown in Fig.11 b); and TEM-EDS mapping images of (b) Ni, (c) Cu, (d) V and (e) O after being used as catalysts for a period of time.
[0035] Fig.14 Shown: X-ray diffraction patterns of NiCuVOx (Example 1) before and after use as catalyst for extended periods of time. Cyclic voltammetry of 1M KOH electrolyte at various scan rates and related calculations of electrochemical surface area (a and b: NF; c and d: CoFe / NF; e and f: CoFeCr / NF).
[0036] Fig.15 ad denotes: (a) K-edge X-ray absorption near-edge structure (XANES) on Ni; (b) extended X-ray absorption fine structure (EXAFS) on Ni; (c) K-edge XANES on V; (d) K-edge XANES on Cu.
[0037] Fig.16 Shown are the LSV curves of NiCuVOx (Example 1) deposited on nickel foam (NF), nickel mesh and carbon fiber paper (CFP) substrates in 1 M KOH.
[0038] Fig.17 : LSV curves comparing the activity of the HER electrode of the present invention (NiCuVOx; Example 1) deposited on a 0.5 cm x 0.5 cm substrate and a 21 cm x 21 cm substrate.
[0039] Fig.18 a and b represent: (a) LSV curves of the HER catalyst of the present invention (Co-V; Example 2) with Co (Example 2) and Pt / C (iR corrected); and (b) Tafel slopes of Co-V and Co prepared according to Example 2.
[0040] Fig.19 Shown are the LSV curves of Co-V and Co prepared according to Example 2 in a neutral electrolyte.
[0041] the term
[0042] As used herein, the term "water splitting" refers to any process that generates elemental hydrogen or oxygen from water as a starting material. The water splitting processes described herein are electrolytic in nature. These electrolytic processes typically include a hydrogen evolution reaction (HER) at the cathode and an oxygen evolution reaction (OER) at the anode.
[0043] As used herein and in the appended claims, the singular forms "a," "an," and "the" include plural references unless the context clearly dictates otherwise. Thus, for example, reference to "a surface" may include a plurality of surfaces or may be reference to one or more surfaces, and so forth.
[0044] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which the invention belongs. It should be understood that any materials and methods similar or equivalent to those described herein can be used to practice or test the present invention; the best known implementations of various materials and methods are described.
[0045] The word "(s)" after a noun refers to the singular or plural form, or both.
[0046] The term "and / or" can mean "and" or "or".
[0047] Unless the context requires otherwise, all percentages stated herein are percentages by material weight.
[0048] Various features of the present invention are described with reference to specific values or ranges of values. The values are intended to be related to the results of various appropriate measurement techniques and should therefore be interpreted as including the error range inherent in any particular measurement technique. Some values described herein are represented by the term "about", at least in part to account for this variability. When used to describe a value, the term "about" can mean an amount within ±25%, ±10%, ±5%, ±1% or ±0.1% of the value.
[0049] The term "comprising" (or variations such as "comprise" or "comprises") used in this specification, unless the context requires otherwise due to express language or necessary implication, is used in an inclusive sense, that is, in various embodiments of the present invention, the presence of the stated features is specified, but the presence or addition of other features is not excluded. DETAILED DESCRIPTION
[0050] The present invention provides a hydrogen evolution reaction (HER) catalyst comprising a catalytic metal species and a vanadium species, wherein the catalytic metal species and the vanadium species are dispersed within the catalyst.
[0051] Surprisingly, the dispersed vanadium and metal catalyst species improve the HER catalytic activity of the material. In addition, the HER catalyst is stable in alkaline and neutral electrolytes even under prolonged electrolysis conditions. The HER catalyst of the present invention can advantageously provide a low-cost and highly active cathode material for industrial-scale water splitting.
[0052] The metal catalyst material and the vanadium material are dispersed in the HER catalyst. In some embodiments, the metal catalyst material and the vanadium material are contained in the particles. In some embodiments, the distribution of the metal catalyst material and the vanadium material is substantially uniform throughout the HER catalyst. The distribution and / or allocation of various atoms contained in the HER catalyst can be determined by TEM-EDS spectra. For example, in one embodiment of the present invention described in Example 1, the embodiment includes nickel and copper alloys as metal catalyst materials and vanadium oxide as vanadium material, and nickel, copper, vanadium and oxygen atoms are substantially uniformly dispersed throughout the catalyst.
[0053] Early reports on the preventive effect of vanadium on nickel catalysts described the formation of vanadium deposits on the cathode surface. However, in the present invention, vanadium species and metal catalyst species are dispersed in the HER catalyst. The dispersion of vanadium species and metal catalyst species can not only prevent the passivation of the catalytic metal species, but also improve its catalytic activity. The increase in catalyst activity is manifested as a related reduction in overpotential to achieve the desired current density.
[0054] The theoretical potential for the electrolysis of water by an electrode is 1.23 V relative to the reversible hydrogen electrode (RHE). Any excess potential above this theoretical limit required to drive water electrolysis by a given electrode is called the overpotential (η). The HER catalysts of the present invention require extremely low overpotentials relative to the RHE.
[0055] In some embodiments, in order for the HER catalyst of the present invention to provide 10 mA cm -2 The current density of 10 mA cm-1 requires an overpotential of about 5 mV to about 50 mV, such as about 5 mV to about 30 mV, or about 8 mV to about 30 mV. Under alkaline conditions, the overpotential of the HER catalyst of the present invention relative to RHE can be about 5 mV to about 14 mV to provide 10 mA cm-1. -2 Under neutral conditions, the HER catalyst of the present invention provides 10 mA cm relative to RHE. -2 The overpotential for a current density of 10 mA cm-1 can be about 10 mV to about 50 mV, for example, about 15 mV to about 40 mV or about 20 mV to about 35 mV. In comparison, for existing commercial Pt / C (20%) electrodes, achieving a current density of 10 mA cm-1 is about 10 mA cm-1. -2 The overpotential required for a current density of about 5mV to 20mV.
[0056] In some embodiments, to provide 100 mA cm -2The HER catalyst of the present invention requires an overpotential of about 15 mV to about 200 mV, such as about 20 mV to about 150 mV or about 30 mV to about 140 mV, to provide a current density of 100 mA cm -2 The current density of the present invention is, for example, about 15 mV to about 44 mV, or about 25 mV to about 4 mV, or about 35 mV to about 44 mV. Under neutral conditions, the HER catalyst of the present invention provides 100 mA cm -2 The overpotential for a current density of 100 mA cm-1 can be about 50 mV to about 200 mV, for example, about 50 mV to about 180 mV or about 100 mV to about 150 mV. In comparison, for existing commercial Pt / C (20%) electrodes, achieving 100 mA cm-1 is -2 The overpotential required for a current density of about 10mV to 50mV.
[0057] The HER catalyst comprises a catalytic metal substance. The catalytic metal substance comprises an active catalyst substance. Any metal substance capable of catalyzing HER can be used as an active catalyst substance. In some embodiments, the catalytic metal substance consists of an active catalyst substance.
[0058] In some embodiments, the active catalyst species is a transition metal species, preferably a first row transition metal. The active catalyst species can be an earth-abundant metal species, such as any metal species capable of catalyzing HER except Re, Ru, Os, Rh, Ir, Pd, Pt, Ag, and Au.
[0059] In a specific embodiment, the active catalyst species is selected from nickel (Ni) and cobalt (Co). Nickel and / or cobalt may be alloyed with any other metal species that does not significantly reduce the catalytic activity of the HER catalyst.
[0060] Typically, the active catalyst material is in metallic form. Therefore, the oxidation state of the active catalyst material is typically zero. However, in some embodiments, the active catalyst material may be included in a non-metallic form, such as an oxide, sulfide, or salt.
[0061] Catalytic metal species are usually provided in crystalline form. The rigid, organized structure of the crystalline metal is believed to further enhance the catalytic activity of the HER catalyst. Crystalline forms with high specific surface areas, such as crystalline nanoparticles, are preferred.
[0062] The HER catalyst also includes a vanadium species. Any vanadium species that can prevent the catalytic metal species from being deactivated can be used.
[0063] In some embodiments, the vanadium material is a vanadium oxide, such as vanadium(II) oxide (VO 2 ), vanadium pentoxide (V 2 O 5 ) or VO 1.95 hydrate.
[0064] Vanadium species by themselves cannot catalyze HER. It is believed that the presence of vanadium species in HER catalysts affects the properties and morphology of the metal catalyst species to prevent its passivation and enhance its catalytic activity.
[0065] The molar ratio of vanadium species to active catalyst species in the HER catalyst may not exceed about 20%. For example, the molar ratio of vanadium species to active catalyst species may be no greater than about 15%, about 12%, about 10%, about 8%, about 7%, about 6%, about 5%, about 4%, about 3%, about 2%, about 1.7%, or less. The minimum amount of vanadium species present in the HER catalyst may be any amount above the detection limit of the vanadium species, for example, by inductively coupled plasma optical emission spectroscopy (ICP-OES). In some embodiments, the molar ratio of vanadium species to active catalyst species may be at least about 0.1%. For example, the minimum molar ratio of vanadium species to active catalyst species may be at least about 0.5%, about 1%, about 1.5%, or about 2%. The molar ratio of vanadium species to active catalyst species may be from any of these minimum amounts to any of the above molar ratios, for example, 0.1% to 20%, 1.5% to 12%, or 2% to 10%.
[0066] In some embodiments, the metal catalyst material further comprises a metal modifier. Without wishing to be bound by theory, it is believed that the addition of a metal modifier in the metal catalyst material affects the metal properties of the active catalyst material. Ideally, the active catalyst material would have a metal property that balances its relative binding affinity to the water reactant and the hydrogen reaction product. Too high a binding affinity to the HER product results in lower catalytic activity. Therefore, the addition of a metal modifier may help optimize the metal properties of the active catalytic material in the metal catalyst material. In some embodiments, the metal modifier may be a metal material that is generally equal to or lower in electronegativity than the active catalyst material. Therefore, the precise selection of the metal modifier depends on the selected active catalyst material. For example, when the active catalyst material comprises nickel or cobalt, the metal modifier may be selected from copper, iron and / or manganese materials.
[0067] The metal modifier may be present in the HER catalyst in any form that enables it to act as a metal modifier of the active catalyst species. Typically, the metal modifier may be in the form of a metal (eg, an alloy with the active catalyst species).
[0068] In some embodiments, the metal catalyst material comprises an alloy of an active catalyst material and a metal modifier. The alloy may have a crystalline morphology.
[0069] The molar ratio of the metal modifier to the active catalyst material may not exceed about 25%. For example, the molar ratio of the metal modifier to the active catalyst material may be no greater than about 24%, about 23%, about 22%, about 21%, about 20%, about 19%, about 18%, about 17%, about 16%, about 15%, about 14%, about 13%, about 12%, about 11%, or about 10.5%. In embodiments comprising a metal modifier, the minimum molar ratio of the metal modifier to the active catalyst material may be at least about 0.1%, for example, at least about 0.5%, 1%, or 5%. The molar ratio of the metal modifier to the active catalyst material may range from any of these minimum amounts to any of the above molar ratios, for example, 0.1% to 25%, 1% to 20%, or 10% to 17%.
[0070] In some embodiments, the metal catalyst material includes nickel, nickel-copper alloy, or cobalt.
[0071] In some embodiments, the metal catalyst material and the vanadium material are in the form of particles. Thus, in some embodiments, the HER catalyst comprises particles comprising a metal catalyst material interspersed with a vanadium material. Typically, the particles will be arranged in an ordered manner.
[0072] The shape of the particles depends on the manufacturing method and the chemical properties of the components. Therefore, the shape of the particles is not limited. For example, when the metal catalyst material includes nickel and copper alloys and vanadium oxide, the particles are spherical.
[0073] The particles can be amorphous, semi-crystalline and / or crystalline. In some embodiments, the particles include a crystalline portion and an amorphous portion. For example, the metal catalyst material can be crystalline, and the vanadium material can be amorphous in the same particle. In some embodiments, the average diameter of the nanocrystals is from about 0.1 nm to about 15 nm, such as from about 0.1 nm to about 12 nm or from about 0.5 nm to about 10 nm. The smaller the particle size, the larger the specific surface area. In the electrolysis process, the larger surface area increases the contact of water with the active catalyst material.
[0074] In some embodiments, the HER catalyst may include a coating to improve the long-term stability and durability of the catalyst, particularly when the catalyst will be used for a long time in an alkaline solution. Suitable coatings include metal oxides, such as chromium oxide (CrO). In some cases, the coating may be used to minimize or reduce the dissolution of vanadium species that may occur over time under alkaline conditions.
[0075] The concentration of each species present in the HER catalyst can be determined by inductively coupled plasma optical emission spectroscopy (ICP-OES).
[0076] A catalytic material comprising a HER catalyst as described herein is also provided. The catalytic material generally also includes a substrate. Any suitable substrate that does not interfere with the HER catalytic activity of the HER catalyst can be used. Suitable substrates include conductive metal substrates (e.g., metal substrates such as foamed metals or metal meshes or fluorine-doped tin oxide (FTO)) and conductive non-metallic substrates (e.g., carbon fiber paper substrates). Suitable foamed metals include nickel foams and copper foams. Suitable metal meshes include nickel meshes.
[0077] Also provided is an electrode comprising a HER catalyst and a conductive substrate. Any conductive substrate that does not interfere with the HER catalytic activity of the HER catalyst, including those described above, may be used.
[0078] Preparation method
[0079] The HER catalyst and materials containing the same may be prepared by any method known in the art, as long as the vanadium species is dispersed in the metal catalyst species.
[0080] In some embodiments, the catalytic materials and / or electrodes of the present invention can be prepared by a simple electrodeposition process.
[0081] Thus, described herein is a method of preparing a HER catalyst comprising a vanadium species of a metal catalyst species dispersed on a conductive substrate, the method comprising electrolyzing a solution comprising a source of the metal catalyst species and a source of the vanadium species in a solution in contact with the conductive substrate. Typically, the solution is an aqueous solution.
[0082] The method generally includes contacting a conductive substrate with a solution in the form of a salt comprising a vanadium salt and a metal catalyst substance, and applying a first voltage between the conductive substrate and a counter electrode through the solution to electrodeposit the vanadium substance and the metal. The dispersion of the catalyst substance on the substrate causes the vanadium substance to be dispersed in the metal catalyst substance. In some embodiments, the method is performed in a three-electrode system, the three-electrode system comprising a working electrode, which comprises a conductive substrate, a counter electrode, and a reference electrode, and applying a first voltage between the working electrode and the reference electrode through the solution to electrodeposit the metal catalyst substance and the vanadium substance onto the surface of the conductive substrate. In other embodiments, the method is performed using a two-electrode system comprising an anode and a cathode of a conductive substrate, and a first voltage is applied to the anode and the cathode through the solution to electrodeposit the metal catalyst substance and the vanadium substance onto the surface of the conductive substrate.
[0083] The first voltage is about -10V to -0.5V. The first voltage can be maintained for a period of time sufficient to electrodeposit a layer of catalyst on the substrate. In some embodiments, the first voltage is maintained for a period of time from 1 minute to about 1 hour, for example, from about 1 minute to about 30 minutes, about 2 minutes to about 15 minutes, or about 10 minutes. The electrodeposition can be carried out at room temperature. As used herein, room temperature refers to an ambient temperature of about 20°C to about 30°C, preferably about 25°C.
[0084] In these preparation methods, the salt form of the metal catalyst material can include a salt of the active catalyst material and optionally a precursor of a metal modifier, such as a salt form of a metal modifier. Therefore, when the metal catalyst material comprises nickel as the active catalyst material, the solution may comprise a nickel salt. Similarly, when the metal catalyst material comprises cobalt as the active catalyst material, the solution may comprise a cobalt salt. Any salt form of the active catalyst material capable of electroreduction can be used. Preferably, the salt is selected from nitrates, chlorides and sulfates or a combination thereof.
[0085] The solution may contain a salt of an active catalyst species (or "active catalyst salt") at a concentration of no more than about 1M. For example, the solution may contain a salt of an active catalyst species at a concentration of no more than about 900mM, about 800mM, about 700mM, about 600mM, or about 500mM. The minimum concentration of the active catalyst salt is the concentration required to electrodeposit enough active catalyst species onto the substrate under an applied voltage. Thus, the minimum concentration of the active catalyst salt may be at least about 10mM, about 15mM, about 50mM, about 100mM, about 200mM, about 250mM, about 400mM, or about 500mM. The concentration of the active catalyst salt may be between any of these minimum concentrations and any other concentration of the active catalyst salt described herein, for example, from 10mM to 1M or 400mM to 600mM.
[0086] The solution may include a salt of a metal modifier (or "metal modifier salt") at a concentration of no more than about 100 mM. For example, the solution may include an amount of a metal modifier salt of no more than about 80 mM, about 70 mM, about 60 mM, about 50 mM, about 40 mM, about 30 mM, or about 20 mM. When present, the minimum concentration of the metal modifier salt may be about 1 mM or about 5 mM. The concentration of the metal modifier salt may be between any of these minimum concentrations to any other concentration of the metal modifier salt described herein, for example, 1 mM to 80 mM or 5 mM to 20 mM.
[0087] The molar ratio of the metal modifier to the active catalyst material in the HER catalyst can be controlled by selecting the appropriate concentration of each precursor in the solution before electrodeposition. In some embodiments, the metal modifier can be selectively removed from the metal catalyst material by a further electrolysis step. Without wishing to be bound by theory, it is believed that the active catalyst material is kinetically stable in the electrodeposited material by interaction with the vanadium material and the metal modifier. In addition, it is believed that at least partial removal of the metal modifier can further increase the surface area of the HER catalyst because the area occupied by the metal modifier before selective removal becomes accessible to water during water splitting electrolysis. In addition, it is believed that after the complex is formed, the metallic properties of the active metal material are not significantly affected by removing the metal modifier. Therefore, in some embodiments, the method includes selectively removing the metal modifier from the metal catalyst material, typically by applying a second voltage to the entire conductive substrate in contact with the solution. The second voltage can be an anode potential of about 0.4V to about 1V, such as about 0.6V. The second voltage can be maintained for a period of time sufficient to remove the desired amount of metal modifier. The second voltage may be maintained for a period of about 1 minute to about 30 minutes, for example, about 200 seconds to about 600 seconds. The electrolytic selective removal of the metal modifier may be performed at room temperature.
[0088] The solution includes a precursor of a vanadium species (or "vanadium precursor"). Any soluble vanadium source may be used; however, the precursor of the vanadium species is typically a vanadium-containing salt, such as ammonium vanadate (NH 4 VO 3 ), vanadium oxide (V 2 O 5 ) or sodium vanadate (NaVO 3 ).
[0089] The solution may contain a vanadium precursor at a concentration of no more than about 50 mM, about 40 mM, about 30 mM, about 25 mM, about 20 mM, about 15 mM, or about 10 mM. The minimum concentration of the vanadium precursor may be at least about 0.01 mM, about 0.1 mM, about 1 mM, or about 2 mM. The concentration of the vanadium precursor may be between any of these minimum concentrations and any other concentration of the vanadium precursor described herein, such as about 0.1 mM to about 50 mM, about 1 mM to about 25 mM, or about 2 mM to about 15 mM. The relative concentrations of the vanadium precursor and the active metal catalyst salt may be selected to provide a desired molar ratio of vanadium species to active catalyst species.
[0090] The solution typically has an acidic pH (i.e., a pH of less than 7). Thus, the solution may include an acid. The concentration of the acid may be from about 100 mM to about 1 M, for example, from about 250 mM to about 750 mM or about 500 mM. Suitable acids include boric acid (H 3 BO 3), hydrochloric acid (HCl), sulfuric acid (H 2 SO 4 ), nitric acid (HNO 3 ) and ammonium ions (e.g., NH4Cl or NH4Br), and combinations thereof.
[0091] The solution may further comprise one or more electrolytes. Suitable electrolytes include salts such as metal nitrates, metal sulfates and / or metal chloride salts. Typically, the metal of the electrolyte salt will correspond to the one or more metals contained in the HER catalyst. The electrolyte may be present at a concentration of about 1M.
[0092] In some embodiments, the method further comprises a substrate pretreatment step, wherein the substrate is washed with a strong acid (e.g., 4M HCl) and sonicated. The pretreatment step typically removes oxides and other impurities from the substrate surface prior to electrodeposition of the HER catalyst.
[0093] In some embodiments, the method further involves including a reference electrode in the electrolytic cell, and the reference electrode is also in contact with the solution. Suitable reference electrodes include Ag / AgCl, reference hydrogen electrode, Ag / Ag 2 SO 4 Electrode, Calomel Electrode, Hg / Hg 2 SO 4 Electrode and Hg / HgO electrode. In a particular embodiment, the reference electrode, when used, is an Ag / AgCl electrode.
[0094] The conductive substrate may be fluorine-doped tin oxide (FTO), stainless steel, metal foam (e.g., nickel foam or copper foam), metal mesh (e.g., nickel mesh or copper mesh), or non-metallic conductive substrate (e.g., carbon fiber paper (CFP) or carbon cloth). After electrodeposition, the conductive substrate may have a carbon fiber content of about 1 mg / cm 2 To about 50mg / cm 2 The mass loading of HER catalyst.
[0095] In some embodiments, the HER catalyst can be coated with a metal oxide. For example, an electrode containing NiCuVOx prepared on a substrate such as nickel foam can be immersed in a metal salt solution. After removal from the solution, the electrode is vacuum dried and annealed at high temperature in an inert atmosphere and then cooled. In a practical embodiment, the NiCuVOx electrode on the nickel foam is coated with chromium oxide by immersing the NiCuVOx electrode on the nickel foam in a chromium (III) sulfate solution (10 mL, 0.005 M) for 1 minute. The electrode is removed from the solution, vacuum dried and annealed at 350°C in an Ar atmosphere for 2 hours with a heating rate of 3°C / min. The electrode is then cooled to ambient temperature.
[0096] How to use
[0097] The present invention provides a method for hydrogen evolution by a water splitting process. The method is performed in an electrochemical cell comprising at least two electrodes and an electrolyte solution, wherein at least one of the two electrodes comprises a HER catalyst of the present invention. In some embodiments, the electrochemical cell is a 2-electrode system comprising an anode and a cathode comprising a HER catalyst of the present invention. In other embodiments, the electrochemical cell is a 3-electrode system comprising a working electrode, a counter electrode, and a reference electrode comprising a HER catalyst of the present invention. The method comprises contacting water with at least two electrodes of the electrochemical cell and applying a voltage to at least two electrodes through an electrolyte solution. Since the HER half-reaction typically occurs at the cathode of a 2-electrode system or the working electrode of a 3-electrode system, the cathode or working electrode comprises a HER catalyst of the present invention. In some embodiments, the electrolyte solution is an aqueous electrolyte solution. The aqueous electrolyte solution may also be a source of water. The electrolyte solution may have a pH of about 7 or greater, for example, a pH of about 7 to about 14. In some embodiments, when the pH is alkaline, the electrolyte solution comprises a strong base, such as a hydroxide base, such as NaOH or KOH. The electrolyte solution may also comprise a vanadium salt (e.g., NH 4 VO 3 ), especially when the electrolyte solution has an alkaline pH. The concentration of the vanadium salt in the electrolyte solution may be up to about 50 mM, such as about 0.2 mM to about 25 mM.
[0098] Typically, the anode used in these methods will contain an oxygen evolution reaction (OER) catalyst such as Ir / C or RuO 2 / C.
[0099] When used in these methods, the HER catalysts of the present invention provide improved catalytic activity to the leading HER catalysts of the present invention. Unexpectedly, the HER catalysts are able to provide such improved catalysis while using earth-abundant metals. Also unexpectedly, the HER catalysts are able to provide improved catalytic activity and require lower overpotentials than other known earth-abundant metal-based HER catalysts, including corresponding Ni- or Co-based systems. In addition, the HER catalysts of the present invention are unexpectedly stable and active under neutral and alkaline electrolysis conditions.
[0100] In some embodiments, the hydrogen evolution method is performed at up to 50 mV dec -1 (e.g., up to 45mV dec -1 、30mV dec -1 or about 25mV dec -1 ) is carried out based on the Tafel slope of . Typically, HER kinetic models indicate that for about 120, 40, or 30 mVdec -1If the Tafel slope is , the Volmer, Heyrovsky or Tafel reaction will be the rate determining step.
[0101] The voltage applied to the anode should be chosen to match or exceed the overpotential of the HER catalyst to drive the HER.
[0102] An electrolyzer is also provided, comprising an anode and a cathode, a power source and an optional reference electrode. Typically, the cathode comprises a HER catalyst of the present invention. In some embodiments, the power source provides electricity generated from a low carbon intensive power source. The power source can be a renewable power source, such as one or more solar panels or wind turbines, or a non-renewable power source, such as a nuclear reactor.
[0103] Example
[0104] The present invention will be further described by way of non-limiting examples. Those skilled in the art will appreciate that many modifications may be made without departing from the spirit and scope of the present invention.
[0105] Example 1 - Nickel-based catalyst
[0106] Material synthesis
[0107] Preparation of NiCuVOx electrodes. All electrodepositions were performed in a standard three-electrode electrochemical setup. NiCuVOx catalysts were electrodeposited on nickel foam (NF) or fluorine-doped tin oxide (FTO) substrates using nickel foam (NF) or fluorine-doped tin oxide (FTO) as working electrodes, graphite plates as auxiliary electrodes, and saturated calomel electrode (SCE) as reference electrodes. Prior to deposition, nickel foam was first sonicated in 5 M HCl solution for 20 min to remove the NiO layer, followed by rinsing with water and ethanol and then drying in air. The electrodeposition and selective dealloying solution consisted of 500 mM NiSO 4 , 8mM~32mM CuSO 4 , 8mMNH 4 VO 3 and 500 mM HO 3 BO 3 Composition. Electrodeposition was performed at room temperature using a CHI 660D electrochemical workstation (CH instrument). First, a NiCuVOx film was electrodeposited onto the NF surface at -2.0 V (vs. SCE) for 600 s. Optionally, Cu in the NiCu film was then selectively dissolved by applying an anodic potential of 0.6 V for 200 s to 600 s at room temperature.
[0108] Preparation of VOx and NiVOx electrodes.VOx and NiVOx electrodes were prepared in the same way as NiCuVOx electrodes. For VOx deposition on FTO, all other conditions were the same except that 8 mM NH 4 VO 3 and 500 mM HO 3 BO 3 The precursors were deposited onto the NF surface at -2.0 V (vs. SCE) for 600 s. For NiVOx deposition, the electrolyte contained 500 mM NiSO 4 , 8 mM NH 4 VO 3 and 500mMH 3 BO 3 , and deposited onto the NF or FTO surface at −2.0 V (vs. SCE) for 600 s.
[0109] Preparation of Ni and NiCu Electrodes. For Ni deposition, the electrolyte contained 500 mM NiSO 4 and 500 mM HO 3 BO 3 , and deposited onto the surface of NF or FTO at -2.0 V (vs. SCE) for 600 s. For NiCu deposition, the electrolyte contained 500 mM NiSO 4 、16mM CuSO 4 and 500 mM HO 3 BO 3 , and deposited onto the surface of NF or FTO at -2.0 V (vs. SCE) for 600 s.
[0110] Chronopotentiometry experiment
[0111] exist Three-electrode system (NiCuVOx as working electrode, graphite plate as reference electrode, SCE as reference electrode) in a 1 M PBS neutral solution at 50 mA cm -2 The results of this experiment are shown in Fig.10 b.
[0112] By using NiCuVOx as the cathode and commercial nickel as the cathode in a two-electrode system at 80 °C in a 30 wt% KOH electrolyte, the current density was increased from 10 mA cm -2 Increase to 500mA cm -2 , further experiments were conducted (the results are shown in Fig.11 a). In addition, using the same battery configuration, the -2 The current density was 300 mA cm for 10 h and then -2The long-term stability of the HER catalyst was evaluated by 10 startup and shutdown cycles at the same current density. Fig.11 b).
[0113] Characterization techniques
[0114] X-ray diffraction spectroscopy (XRD). XRD measurements were performed using a PANalytical X'Pert Empyrean instrument equipped with a standard Cu anode and a K-α wavelength of 1.54 nm. The typical scan range was 10° to 80° at 0.039° s -1 The step size is collected.
[0115] X-ray photoelectron spectroscopy (XPS). XPS measurements were performed using a Thermo ESCALAB250i X-ray photoelectron spectrometer and to ensure the consistency of the results, scans were performed at 4 different points.
[0116] Raman spectroscopy. Raman spectroscopy was performed using a 1800 l mm -1 A Renishaw inVia Raman microscope with a 514 (green) Ar-ion laser. All Raman samples were catalysts supported on CFP.
[0117] Transmission electron microscopy (TEM). TEM was performed using a Phillips CM 200 microscope. To prepare the TEM sample, the electrode was physically scratched with a sharp knife and the catalyst supported by nickel foam (NF) was transferred to a Cu grid. The resulting powder was dispersed in anhydrous ethanol for 15 min using ultrasound. The resulting mixture was then dropped onto the Cu grid and dried at room temperature.
[0118] High-resolution transmission electron microscopy (HRTEM). HRTEM was performed with a Phillips CM 200 microscope. To prepare the HRTEM samples, the NF-supported HER catalyst was transferred to a Cu grid coated with holey carbon by sonicating the sample from the NF in anhydrous ethanol for 15 min. The resulting mixture was then drop-cast onto the Cu grid and dried at room temperature.
[0119] Scanning Electron Microscopy SEM analysis was performed using a JEOL F7001 at an accelerating voltage of 17 kV.
[0120] Optical microscope. Microscope images were taken with a Nikon eclipse LV100POL.
[0121] X-ray absorption near-edge structure (XANES) and extended X-ray absorption fine structure (EXAFS).XANES and EXAFS were recorded on the multiple Wiggler-XAS beamline 12ID at the Australian Synchrotron.
[0122] Inductively coupled plasma optical emission spectroscopy (ICP-OES). ICP-OES was performed on a Perkin Elmer Optima 7300DV inductively coupled plasma optical emission spectrometer by dissolving the samples in 10 mL of aqua regia acid solution before analysis.
[0123] Results and Discussion
[0124] The successful deposition of the vanadium composite was confirmed by cyclic voltammetry and the observed color change of FTO before and after electrodeposition. Figure 1 The cyclic voltammogram (CV) shows that the absence of vanadium precursors results in no obvious redox peaks, indicating that no electrochemical reaction occurs. However, in the presence of vanadium ions, a significant reduction peak appears at -2.0 V in the CV, which is believed to be due to the reduction of vanadate ions ( Figure 1 ).
[0125] The successful formation of vanadium-doped nickel and nickel-copper alloy materials is demonstrated by the color difference of the vanadium-containing material deposited on FTO (black) compared to the material deposited on FTO without vanadium (gray-silver).
[0126] The structure of the prepared electrodes was also characterized by X-ray diffraction (XRD) technique. Samples deposited on FTO glass were used for XRD studies because the NF substrate would interfere with the diffraction pattern. Figure 2 As shown in Figure 2, the XRD patterns of Ni and NiCu electrodes show three main diffraction peaks at 2θ = 44.44°, 51.26° and 76.35°, which are very consistent with the (111), (200) and (220) planes of face-centered cubic nickel (JCPDS, No. 70-0989). As for NiCu, in addition to the three characteristic peaks of Ni, three other characteristic peaks appear at the bottom of the Ni (111), (200) and (220) peaks, indicating the formation of Ni and Cu alloys. For the vanadium-containing sample, the XRD pattern shows only a small and broad peak at 44.44°, indicating that NH 4 VO 3 Ultrafine Ni-like nanocrystals (NCs) were formed when V was present. The average size of the ultrafine NCs was calculated based on the Scherrer equation to be only ~4.65 nm, which is much smaller than ~26.79 nm of pure nickel and ~19.07 nm of NiCu alloy. The molar ratio of V:Ni precursor used to form ultrafine Ni-like NCs during electrodeposition was only 1.7% (i.e., 1.7:100 mole NH 4 VO3 :100 mol NiSO 4 ), indicating a strong influence of vanadium on the crystal evolution ( Figure 3 ). Ultrafine NCs are believed to increase the exposure of active centers in the catalyst structure. In order to further provide more exposed active centers, copper was selectively dealloyed using the above-mentioned anodic dissolution process. The copper / nickel ratio before and after dealloying was analyzed using inductively coupled plasma optical emission spectroscopy (ICP-OES) technology, which dropped from 15.4% to 10.55% (see Table 1 below), confirming partial copper removal. It is worth noting that the presence of copper in the catalyst plays an important role in catalyzing the hydrogen evolution reaction, which will be discussed below; however, no difference in its catalytic effect was observed between the partially removed copper catalyst and the catalyst before copper removal. The partially removed copper catalyst is referred to as NiCuVOx in this example.
[0127] Table 1: ICP-OES results of two samples of nickel-copper-vanadium composite materials prepared according to this example.
[0128]
[0129] The electrodeposited samples containing vanadium (NiVOx and NiCuVOx) resulted in the formation of ultrafine NCs, which was confirmed by surface morphology studies. Figure 4 a and Figure 5 From the SEM images in ac, it can be seen that fine NCs with a size of about 5 nm were obtained, while larger crystals of Ni and NiCu were observed, indicating that the presence of vanadium in the composite material played a role in grain refinement. The morphology and structure of the prepared NiCuVOx were further studied using TEM and high-resolution TEM (HRTEM). Low-resolution TEM clearly shows the fine crystal structure of NiCuVOx ( Figure 4 b). HRTEM examination showed that ultrafine NiCuVOx nanocrystals with a size of ~4-5 nm were formed ( Figure 4 c), which is in good agreement with the XRD and SEM results. In the ultrafine NC structure of NiCuVOx, resolvable and unresolvable lattice fringes coexist, which means that these NCs have a crystalline structure accompanied by a substantially uniformly distributed amorphous vanadium deposit. Further investigation of the HRTEM results showed that the d spacing is 0.202nm ( Figure 4 c, inset), corresponding to the (111) plane of fcc Ni. A typical TEM-EDS image shows the uniform distribution of Ni, Cu, V, and O elements ( Figure 4 For Cu, since less Cu is observed in the high brightness Ni sites, part of Cu has been anodically removed from the NiCu alloy.
[0130] By X-ray photoelectron spectroscopy (XPS, Figure 6 ad) studied the composition and element oxidation state of NiCuVOx. For Ni2p XPS ( Figure 6 a), the binding energies at 852.8 eV (Ni2p3 / 2 line) and 870.0 eV (Ni2p1 / 2 line) are related to metallic Ni, and the Ni2p peak split spin-orbit component is 17.3 eV, indicating the formation of nickel metal in the NiCuVOx composite. Figure 6 b shows the Cu 2p3 / 2 and Cu 2p1 / 2 spectral regions of copper at peaks at 932.8 eV and 952.6 eV, respectively, where the Ni2p peak split spin-orbit component is 19.8 eV, indicating that the oxidation state of copper is copper (0) metal. 3 / 2 The binding energy shows two peaks at 516.9 and 515.2 eV ( Figure 6 c), indicating the presence of V 4+ and V 3+ The mixed valence state, where V 4+ The main valence state (V 4+ / V 3+ =9), which is consistent with the black color of the deposited vanadium composite material, indicating that during the electrochemical deposition process, V 5+ The reduction was successful. The fitting peak of O1s ( Figure 6 d) The peak at 529.7 eV points to the OV bond, the peak at 531.2 eV corresponds to the formed vanadium oxide-containing deposit, and the peak at 532.9 eV can be assigned to the surface adsorbed H 2 Oxygen species in O molecules. Based on the above results, the molecular formula of the electrodeposited vanadium-containing complex can be written as VO 1.95 ·xH 2 O.
[0131] The catalytic performance of the prepared NiCuVOx, NiCu, NiV, and Ni catalysts for HER in alkaline, neutral, and corrosive seawater media was evaluated using linear sweep voltammetry (LSV) and chronopotentiometry techniques. For comparison, the electrocatalytic activity of a commercial benchmark Pt / C catalyst (20 wt% Pt on carbon black) was also measured ( Figure 7 a). For NiCuVOx, the optimized electrodeposition and dealloying conditions were first evaluated and it was found that the Cu 2+ / Ni 2+ = 2.5% (16 mM Cu) molar ratio and 400 s anodic dealloying time produced the catalyst with the strongest hydrogen production performance ( Figure 8 ). After optimization, the catalytic activities were compared in 1.0 M potassium hydroxide (KOH), and the overpotential of NiCuVOx for HER was almost zero. Impressively, the NiCuVOx catalyst achieved 10 mA cm at an overpotential of 22 mV (without iR correction).-2 The current density is lower than that of NiVOx, NiCu and nickel, which are 49, 49 and 87 mV respectively. If the resistance between the electrolyte and the electrode is removed (iR compensation, Figure 7 The black dashed line in a shows that only 10 mV overpotential is required to reach 10 mA cm -2 For NiCuVOx catalyst, an overpotential of 42 mV is required to reach a current density of 100 mA cm -2 The iR-corrected overpotential of the NiVOx catalyst is 44 mV, reaching 10 mA cm -2 and 101 mV, reaching 100 mA cm -2 of current density.
[0132] The Tafel slope is considered an intrinsic property of the electrode reaction, and the value of the Tafel slope is determined by the rate-limiting step. Typically, HER kinetic models suggest that the Volmer, Heyrovsky, or Tafel reactions will have Tafel slopes of approximately 120, 40, or 30 mV dec, respectively. -1 The Tafel slopes of NiCuVOx, NiVOx, NiCu, Ni, and 20%Pt / C are 24, 45, 72, 74, and 34 mV dec, respectively. -1 ( Figure 7 b) The minimum Tafel slope of NiCuVOx is 24mV dec -1 , indicating that the hydrogen production rate increases rapidly with the increase of the applied overpotential, and the Volmer-Tafel mechanism is that NiCuVOx nanoparticles generate H at low overpotential. ads Chemical compounding of rate-determining steps.
[0133] Electrocatalytic stability is an important indicator of HER catalysts. The vanadium deposits on FTO (VOx; prepared by electrodeposition) were first immersed in an electrolyte solution (1M phosphate buffered saline (PBS) solution and 1M potassium hydroxide) to test their stability. The FTO substrate was chosen because of its transparency. The VOx deposited on FTO can be immersed in a neutral 1M PBS solution for more than 6 months without any visual changes, while the black VOx deposited on FTO becomes colorless after being immersed in 1M KOH for a period of time, indicating that the vanadium deposits dissolve under alkaline conditions. In addition, under alkaline conditions, it was found that NiCuVOx does not dissolve in alkaline electrolytes ( Fig. 9 ) for a longer time at a constant current density in ). This phenomenon can be further confirmed by the weak XPS V2p signal detected after long-term stability in alkaline, which means that the deposited vanadium oxide (at least on the surface) is almost dissolved into the solution. However, this problem can be solved by adding NH4 VO 3 To solve ( Fig. 9 ).like Figure 7 c, d, and 9 show that the NiCuVOx electrode is subjected to multiple current test conditions or in the presence of NH 4 VO 3 Low (50mA cm -2 ) and high current density (100 mA cm -2 ) shows good stability and mass transfer performance, which is in sharp contrast to the poor stability of the nickel electrode measured under the same conditions. 4 VO 3 In this case, NiCuVOx exhibits excellent long-term electrochemical robustness, with a stable overpotential of about 190 mV at 50 mA cm in chronopotentiometry experiments. -2 More than 20h( Fig.10 b).
[0134] In addition, the effect of VOx dissolution in alkaline on long-term stability can also be solved by coating a layer of amorphous chromium oxide on NiCuVOx (named: CrO-NiCuVOx). Fig.11 As shown in the figure, as the hydrogen evolution reaction (HER) stability test was extended, the HER activity continued to increase before stabilization, and the activity increased by 25% from the beginning. Its excellent durability makes it have broad prospects in practical water electrolysis applications.
[0135] The existing electrochemical water splitting process produces hydrogen under caustic alkaline or caustic acid conditions. Corrosion under such caustic conditions hinders large-scale hydrogen production from abundant water sources such as seawater with a pH close to neutral. The mechanism of HER in alkaline media is similar to that under neutral conditions. Therefore, at pH = 7, the HER activity of the catalyst before and after vanadium modification was further investigated. The prepared electrode can also be used as an electrocatalyst for hydrogen production under neutral pH conditions. Fig.10 As shown in a, NiCuVOx only needs a small amount of η = 56 mV overpotential to reach 10 mA cm -2 This is advantageous compared with η = 284 mV for pure Ni electrode, η = 202 mV for NiCu electrode and η = 114 for NiVOx electrode. If iR compensation is used, the ultra-low overpotential of hydrogen evolution of NiCuVOx catalyst is 10 mA cm-1 at pH = 7. -2 28mV at 100mA cm -2 It is 126mV.
[0136] Currently, hydrogen production from seawater electrolysis remains a challenging task. The main problem in seawater environments is that most water-splitting catalysts are prone to deactivation or corrosion, resulting in reduced efficiency. Therefore, it is very necessary to develop a catalyst with high activity and high stability in simulated seawater or natural seawater environments. The preparation of efficient and stable NiCuVOx hydrogen evolution electrodes was further studied in simulated seawater and natural seawater from Sydney and the South Pacific, China. Interestingly, for NiCuVOx, an overpotential of 194 mV (without iR correction) was required to achieve 10 mA cm-1 under simulated seawater and natural seawater conditions. -2 The current density ( Fig.10 c), which compares favorably with other reported catalysts under similar conditions. Long-term stability tests showed that the catalytic activity in seawater decreased slightly ( Fig.10 d); however, this decrease is believed to be due to the continuous formation of precipitates during the reaction, which form white precipitates on the electrode surface during electrolysis. The formation of precipitates is believed to be due to the complex composition of seawater containing Na, Ca, and Mg salts. However, these white deposits are easily removed by ultrasound, and the high catalytic activity of the catalyst is restored after the removal of the precipitates, demonstrating the robustness of the NiCuVOx electrode.
[0137] In order to further evaluate the robustness and high activity of the prepared NiCuVOx material as a cathode electrode in actual industrial alkaline water electrolysis, actual industrial alkaline water electrolysis was carried out at a high current density (300 mA cm -2 The hydrogen production capability was tested using a two-electrode electrolyzer by comparing with a commercial electrode (Suzhou Jingli Hydrogen Equipment Co., Ltd.) at 80 °C, high electrolyte concentration (30 wt% KOH), and high temperature operation (80 °C). The only difference between the cell setup and the commercial configuration was that the cathode was exchanged with the prepared NiCuVOx electrode on NF, but the Ni on the nickel mesh anode was kept unchanged. First, in a 30 wt% KOH electrolyte at 80 °C, the hydrogen production capability was tested at 10 mA cm -2 Up to 500mA cm -2 The electrolytic activity of the NiCuVOx cathode electrode was measured at different current densities compared with that of the commercial electrode. Fig.12 As shown in a, when NiCuVOx electrodes are used, the water splitting performance is significantly improved over that of commercial cathodes. For example, only 1.35 V of cell voltage is required to deliver 10 mA cm when NiCuVOx is used at the cathode, compared to 1.52 V when the commercial cathode is used. -2 Similarly, a cell voltage of 1.89 V was required to deliver 500 mA cm using the NiCuVOx cathode, compared to 2.08 V for the commercial cathode. -2The increased catalytic activity of NiCuVOx results in energy savings of about 10% compared to commercial cathodes. The hydrogen produced by the nickel-oxygen cathode in the electrochemical cell was quantified by gas chromatography, yielding a Faradaic efficiency of nearly 100%.
[0138] An important goal for all electrolysis processes is to develop catalysts that can withstand long-term operation and frequent / rapid shutdowns / startups, as electrodes can depolarize and easily corrode / deactivate due to reverse current during intermittent operation. In addition, electrodes that can withstand sudden power supply changes are important for use in conjunction with electricity generated from intermittent renewable resources such as solar and wind power. Therefore, in a 30 wt % KOH electrolyte (80 °C, 300 mA cm -2 The stability of the shutdown / startup of continuous and intermittent electrolysis at high temperature and high current density was tested with at least 10 shutdown / startup cycles and a shutdown interval of 1 h. The constant current curves obtained from these tests are shown in Fig.12 b. Through these tests, the cell voltage remained stable at about 1.78 V after each shutdown. These results indicate that the cell potential changes little during the harsh continuous alkaline water electrolysis operation, indicating that the prepared NiCuVOx electrode has good long-term robustness.
[0139] The stability and robustness of the NiCuVOx catalyst were further supported by repeated characterization studies after its use in catalyzing HER. TEM images of NiCuVOx after long-term alkaline water electrolysis showed that the catalyst maintained its structure with uniform distribution of Ni, Cu, V, and O elements ( Fig.13 In addition, the XRD pattern of the NiCuVOx sample after the stability test completely matches the XRD pattern before the test, with the Ni(111) peak being the only peak, further demonstrating the stability of NiCuVOx as a cathode material ( Fig.14 ).
[0140] In order to obtain further information on the oxidation states of the elements and in particular to determine the impact of the deposited vanadium-containing compounds on the HER, Ni, Cu and V K-edge XANES measurements, which are sensitive to the oxidation states of the elements, were performed. Fig.15 a shows the Ni-K edge spectra of different samples and standard NiO. All spectra show a leading edge shoulder, which is attributed to the transition from the 1s core level to the bound state d state near the Fermi level, which means that the oxidation state of the prepared nickel catalyst is similar to that of nickel metal. However, due to the presence of vanadium, the leading edge position shifts to higher energy, and after co-deposition of Cu, the leading edge position shifts to a negative position. This phenomenon indicates that when Cu is present, Ni tends to show more metallic characteristics, which is beneficial for H adsorption, but the strong chemical bond of Ni-H hinders H 2For NiVOx, the white line peak intensity is higher than that of NiCuVOx and NiCu, indicating that Ni is in a higher oxidation state, which means that H 2 Desorption is enhanced, but H adsorption is weakened. Therefore, it is believed that the metallic properties of Ni in the NiCuVOx material correspond to the optimal hydrogen binding energy. For the NiCuVOx composite, the front edge of Ni is located between the front edges of the NiCu alloy and NiVOx, indicating that in the electrochemical water splitting performance, the oxidation state of Ni is slightly oxidized, which significantly affects the activity of catalytic water splitting. The partial oxidation and structural disorder of Ni can also be seen from the EXAFS analysis of the Ni-K edge, indicating that n reduces the Ni-Ni interaction peak intensity and shortens the bond length compared to Ni foil ( Fig.15 b).
[0141] The vanadium K-edge was measured in the prepared catalysts. Fig.15 c shows the spectra of NiCuVOx and NiVOx samples, as well as different valence states of vanadium as a reference sample. It is known that the pre-peak of the V K-edge is a formally forbidden 1s-3d electronic transition, and the intensity of this pre-peak increases from perfect octahedral symmetry (VO) to distorted octahedral VO. 6 Group (V 2 O 3 and VO 2 ), and further increased to the distorted square cone VO 5 Group (V 2 O 5 ) is the lower coordination. Fig.15 c can be seen, according to the XPS results, compared with the reference V 2 O 5 Compared with the previous peak, the intensity of the peak shifts to a lower energy position and decreases slightly, which means that the oxidation state of vanadium decreases and forms VO 2 Like structure.
[0142] The Cu K-edge signal was also measured and the results are as follows Fig.15 d, and a metallic Cu reference is added for comparison. The spectral profile and edge position indicate that copper is close to the oxidized Cu 0 .
[0143] The electrodeposition method allows the electrode materials to be deposited on a variety of conductive substrates including fluorine-doped tin oxide (FTO), nickel foam (NF), nickel mesh, and carbon fiber paper (CFP). Electrodes produced in this way exhibit similar high performance ( Fig.16 The deposition process is also scalable, and NiCuVOx can be successfully deposited onto large substrates with dimensions of 21 cm × 21 cm, showing nearly identical HER activity to that observed for small electrodes prepared in 1 M KOH ( Fig.17).
[0144] Example 2 - Cobalt-based catalyst
[0145] A vanadium oxide doped cobalt catalyst was prepared using a method similar to that described in Example 1. A reference material without vanadium doping was prepared for comparison. Fig.18 and 19 The results shown indicate that the vanadium-doped cobalt catalyst has superior HER catalytic activity to that of the cobalt-only catalyst under both alkaline and neutral conditions. Furthermore, under alkaline conditions, the CoV catalyst has an activity competitive with that of the commercial platinum catalyst.
[0146] CoV cathode preparation. All electrodepositions were performed in a three-electrode electrochemical setup as described in Example 1. The CoV catalyst was electrodeposited onto a nickel foam (NF) substrate using a nickel foam as the working electrode, a graphite plate as the auxiliary electrode, and a saturated calomel electrode (SCE) as the reference electrode. Prior to deposition, the nickel foam was first sonicated in a 5 M HCl solution for 20 min to remove the NiO layer, followed by rinsing with water and ethanol and then drying in air. The electrodeposition electrolyte consisted of 500 mM CoCl 2 、18mmNH 4 VO 3 and 500mm H 3 BO 3 Composition. Electrodeposition was performed at room temperature using a CHI 660D electrochemical workstation (CH instrument). The CoV film was electrodeposited on the NF substrate at 2.0 V (vs. SCE) for 600 s. The molar ratio of V / Co in the precursor was 3.6%.
[0147] Cobalt was prepared on NF control samples. In addition to adding NH 4 VO 3 In addition to the vanadium precursor, a Co control electrode was prepared on NF under the same conditions as above.
Claims
1. A hydrogen evolution reaction catalyst comprising: a catalytic metal substance comprising nickel and copper as active catalyst substances, and an amorphous vanadium material, wherein the vanadium material is vanadium oxide; Wherein, the catalytic metal substance and the vanadium substance are dispersed in the hydrogen evolution reaction catalyst.
2. The hydrogen evolution reaction catalyst according to claim 1, wherein The catalytic metal species and the vanadium species are contained within the particles.
3. The hydrogen evolution reaction catalyst according to claim 2, wherein The particles have a crystalline structure and an amorphous vanadium species.
4. The hydrogen evolution reaction catalyst according to claim 2 or 3, wherein The average diameter of the particles is 0.1 nm to 15 nm.
5. The hydrogen evolution reaction catalyst according to any one of claims 1 to 3, wherein The catalytic metal material includes an alloy of nickel and copper.
6. The hydrogen evolution reaction catalyst according to any one of claims 1 to 3, further comprising a metal oxide coating.
7. The hydrogen evolution reaction catalyst according to claim 6, wherein The metal oxide coating is a chromium oxide coating.
8. A catalytic material comprising the hydrogen evolution reaction catalyst according to any one of claims 1 to 7 and a substrate.
9. An electrode comprising a conductive substrate and the hydrogen evolution reaction catalyst according to any one of claims 1 to 7.
10. A method for preparing a hydrogen evolution reaction catalyst according to any one of claims 1 to 7, a catalytic material according to claim 8, or an electrode according to claim 9, the method comprising contacting a conductive substrate with a solution containing a catalytic metal substance source and an amorphous vanadium substance source, and applying a voltage between the substrate and a counter electrode through the solution to electrodeposit the catalytic metal substance and the amorphous vanadium substance onto the surface of the conductive substrate.
11. A method for separating hydrogen from water, the method comprising: An electrochemical cell comprising at least two electrodes and an electrolyte solution is provided, water is brought into contact with the at least two electrodes, and a voltage is applied between the at least two electrodes, wherein at least one of the at least two electrodes comprises a hydrogen evolution reaction catalyst according to any one of claims 1 to 7, a catalytic material according to claim 8, or an electrode according to claim 9.
12. An electrolyzer comprising at least two electrodes and a power supply, wherein: At least one of the at least two electrodes comprises the hydrogen evolution reaction catalyst according to any one of claims 1 to 7, the catalytic material according to claim 8, or the electrode according to claim 9.
Citation Information
Patent Citations
Heterostructures for ultra-active hydrogen evolution electrocatalysis
CN106605011A